2017
DOI: 10.1002/jsfa.8468
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of phenolic composition in Carignan noir grapes (Vitis vinifera L.) from six wine‐growing sites in Maule Valley, Chile

Abstract: BACKGROUND: Among Chilean varieties, Carignan noir has had a major resurgence due to its rediscovered wine quality potential. For this, the aim of this study was to characterize phenolic composition of grapes grown in six sites from the Maule Valley.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 32 publications
(36 reference statements)
4
45
1
Order By: Relevance
“…These authors reported that during ripening on 'Carignan' and 'Grenache' grapevine, berry composition is more influenced by terroir in terms of early or late ripening, than bunch uniformity. Besides, Martínez-Gil et al (2017) showed that in the warmer sites planted with 'Carignan' vineyards, the grapes presented a more advanced technological maturation at harvest than the coldest places. Moreover, van Leeuwen et al (2004) reported that ripening speed was more influenced by cultivar and vintage compared to soil factor.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These authors reported that during ripening on 'Carignan' and 'Grenache' grapevine, berry composition is more influenced by terroir in terms of early or late ripening, than bunch uniformity. Besides, Martínez-Gil et al (2017) showed that in the warmer sites planted with 'Carignan' vineyards, the grapes presented a more advanced technological maturation at harvest than the coldest places. Moreover, van Leeuwen et al (2004) reported that ripening speed was more influenced by cultivar and vintage compared to soil factor.…”
Section: Discussionmentioning
confidence: 99%
“…It is probably that the high temperatures reached in Cur sites, did not allow a greater accumulation of anthocyanins despite having a more rapid grape ripening than the other sites. Besides, Martínez-Gil et al (2017) found that anthocyanins concentration in 'Carignan' grapes at harvest were related to the accumulation of biologically effective degree days. Andrés-de Prado et al (2007) showed that the soils with higher water holding capacity (Whc), produced wines with lower color intensity and shade, as well as lower total phenolic composition than the wines from the rest of soils.…”
Section: Grape Anthocyanins Contentmentioning
confidence: 99%
See 3 more Smart Citations